Good Governance of Village Fund to Achieve the Village Sustainable Development Goals (SDGs)- Systematic Review - Kurniawati, Susilaningtyas Budiana; Supartini, Supartini; Abdullah, Syahriar; Widyaswati, Rahmatya; Maryanti, Istinganah Eni; Warsina, Warsina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to focus on the achievement of village SDGs through village funds. The village fund program is a strategic policy to accelerate village development based on the Village Law. Currently, village development is aligned with the concept of Sustainable Development Goals (SDGs). This policy is contained in Ministerial Regulation No.8/2022 on the priority use of village funds. The researcher's alternative solution is to apply the principles of good governance of village funds to achieve village SDGs. Therefore, this study aims to determine the theoretical application of good management of village funds to achieve village SDGs. The method used in this research is a systematic review with meta-synthesis that is expected to show theoretical solutions from previous research on accelerating village SDGs through village funds. The result of this research is that village SDGs are important in village development. The application of accounting knowledge is needed to achieve village SDGs. The use of village funds can be applied to achieve village SDGs. Using village funds with good governance can significantly influence achieving village SDGs.